THE MULTICULTURAL LEADERSHIP STRUCTURAL EQUATION MODEL OF PRIVATE ISLAMIC SCHOOL ADMINISTRATORS - Suhairee Beungacha; Suntaree Wannapairo; Rungchatchadaporn Vehachart; Sinchai Suwanmanee (Universitas Islam Negeri Alauddin Makassar, 2022)
The objectives of this research on multicultural leadership structural equation model of private Islamic school administrators were 1) to investigate the components and factors affecting multicultural leadership of private Islamic school administrators, 2) to develop a multicultural leadership structural equation model of private Islamic school administrators, and 3) to examine the consistency of the multicultural leadership structural equation model of private Islamic school administrators developed by the researcher with empirical data. The research was divided into3 phases as follows: Phase 1 was to investigate the components and factors affecting multicultural leadership of private Islamic school administrators using a semi-structured interview with 12 experts; Phase 2 was to develop a multicultural leadership structural equation model of private Islamic school administrators using a focus group discussion with 10 experts; and Phase 3 was to examine the consistency of the multicultural leadership structural equation model of private Islamic school administrators developed by the researcher with empirical data from a sample of 245 people.